A case of successful Thrombolysis in Pulmonary Embolism with Tenecteplase During Peripartum Period - Ngow, Harris Abdullah; Wan Nowalid, Wan Khairina (Republic of China Society of Cardiology, 2011)
Tenecteplase is a recognized thrombolytic therapy for myocardial infarction. It is also increasingly used in massive and submassive pulmonary embolism. Thus far, there had been 22 patients with pulmonary embolism treated with tenecteplase. However, none of the patients was treated during peripartum period. We report its use in a 35-year-old multiparous woman who was referred at 4 hours post partum with cardiogenic shock. She was clinically suspected to have acute pulmonary embolism, and this was confirmed by computed tomography of the pulmonary artery. She was successfully thrombolysed with tenecteplase but suffered bleeding complication. She was resuscitated and remained stable until discharge 1 week later. A repeat computed tomography of the pulmonary artery at day 4 post-thrombolysis showed a significant reduction in the thrombus load. This case illustrates the potential benefit and efficacy of tenecteplase in acute pulmonary embolism in peri-partum women.